NOTE ON HYMENODICTYON (RUB.) AND ITS OCCURRENCE IN MALESIA, ESPECIALLY IN WEST JAVA - C. G. G. J. VAN STEENIS (BRIN Publishing (Penerbit BRIN), 1972)
The genus Hymenodictyon is a genus of often large, often deciduous trees which is widely distributed over the African and Asian-Malesian tropics, with 11 species recorded for Madagascar.